Knowledge and practices regarding insertion and care of indwelling urinary catheter in female patients at a teaching hospital - Rohan, J.P.; Amarasekara, A.A.T.D. (Proceedings of the Scientific Sessions 2016, FMS, USJP in collaboration with SJGH, 2016)
Attached

Objectives: Catheter Associated Urinary Tract Infection (CAUTI) is the most common hospital acquired infection in world wide. Adhering evidence based practice guidelines and correct practice regarding insertion and care of indwelling catheter minimize CAUTI. The objectives of this study were to determine knowledge and practices of nurses regarding insertion and care of indwelling urinary catheter in female patients at Colombo South Teaching Hospital. Methods: The study was a descriptive cross-sectional study using pre-tested semi-structured questionnaire to collect information about knowledge and practices of nurses regarding insertion and care of indwelling urinary catheter in female patients at Colombo South Teaching Hospital, Sri Lanka. There were 122 participants from selected wards/units. The study was conducted at Colombo South Teaching Hospital Sri Lanka. This study was approved by Ethics Review Committee, Faculty of Medical Sciences, University of Sri Jayewardenepura. Results: The response rate was 66.6%. Based on the scoring system, knowledge level on indwelling urinary catheter insertion was 36.1% and it was at fair category level. Most participants (79.5%) had satisfactory level of practices regarding indwelling urinary catheter insertion. Eighty-two present of the participants had unsatisfactory level of knowledge regarding indwelling urinary catheter care. Majority of the participants (78.7%) had satisfactory level of practices regarding indwelling urinary catheter care Conclusions: The findings highlighted that most nurses in this study showed satisfactory level of practices regarding indwelling catheter care. However significant level of knowledge deficit found on indwelling urinary catheter insertion and care. This points to an urgent need of education and training on catheterization and catheter care for nurses in Sri Lanka.